SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM - Lutfiatur Rofiah (Universitas Negeri Gorontalo, 2022)
The conditions that occur in the world of education are still far from what is expected, first conceptually, Islamic Religious Education material is able to be well absorbed by students but has not been able to form a mindset that is actualized in their behavior, religious education currently taking place tends to prioritize aspects of cognition. than affective and psychomotor. We can see how many students get good grades in (cognitive) report cards but we see immoral behavior happening in every corner of this country, from fights between students, promiscuity, to the loss of good manners to parents, which in theory they memorized by heart. If we as teachers want to be humble and want to pray, there must be something wrong in our learning so far. This study aims to describe the components of the performance of Islamic Religious Education teachers at MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency which is supervised by the Madrasah head, describe the strategies/techniques for academic supervision of the head of MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency in improving the performance of Islamic Religious Education Teachers, describes the follow-up to the academic supervision of the head of MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency in improving the performance of Islamic Religious Education Teachers. This study uses a qualitative research approach with the type of case study design. The method of data collection in this study was carried out using three methods, namely observation, interview, and documentation. Data analysis through data reduction (data reduction), data presentation (data display) and data conclusions or verification (consclution drawing & verifying). The results showed that the components of the performance of Islamic Religious Education teachers at MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency, which were supervised by the madrasa head: (a) the ability to plan lessons, (b) the ability to carry out learning, and (c) the ability to assess or evaluate learning. In carrying out the process of supervising the madrasah principal, he collaborates between group techniques and individual techniques that have been applied at MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency. The follow-up to the academic supervision of the head of MI Al-Khoiriyah Putukrejo, Gondanglegi District, Malang Regency in improving the performance of Islamic Religious Education teachers: (a) providing guidance and guidance on planned learning planning, implementing learning, making learning evaluations. (b) The Head of Madrasah provides opportunities for Islamic Religious Education teachers to take part in training in making lesson plans, implementing learning, and making learning evaluations.